The Role of Saints and Sufis for the Propagation of Islam in Kashmir during the Age of Sultans: کشمیر میں سلاطین کے عہد میں اشاعت اسلام کے لیے اولیاء اور صوفیا کا کردار - Khawaja, Dr. Anbreen; Gull, Dr. Shabnum; Zahoor, Dr. Najma (Al Khadim Research Journal of Islamic Culture and Civilization, 2024)
Kashmir, often known as the "land of dreams," enthralls and enchants people with its ageless beauty. The world has known Kashmir for its unique topography, civilization, culture, and populace since prehistoric times. Following the arrival of Muslim rulers in Kashmir, a significant influx of Islamic preachers from Central Asia contributed significantly to the structural change of the region by spreading Islam. Islam reached its zenith in Kashmir in 1339, although it was primarily introduced to the area in the eighth century. In addition to Sufis, Muslim officials, traders, and travelers were played significant role in spreading Islam. In Kashmir, Islam advanced significantly in the age of sultans. Madrasahs and Mesajid were founded in Kashmir to propagate Islamic principles. This paper mostly relies on secondary sources.